Hadith on the Recommendation to Increase Istighfar, Narrated by Imam Ahmad No. 2234 (A Study Of The Understanding of Hadith Using Jasser Auda’s Maqāṣhid Approach) - Hasan Su'aidi; Yuliyanah Yuliyanah; Luhur Kharisman (Religia: Jurnal Ilmu-Ilmu KeIslaman, 2026)
This research focuses on understanding the hadith recommending more istighfar using Jasser Auda's maqāṣhid approach, with the aim of finding out the understanding of the hadith recommending making more istighfar narrated by Imam Ahmad no. 2234 with Jasser Auda's maqᾱṣhid approach. This research aims to understand the importance of istighfar in various aspects of human life, from spiritual to economic dimensions, as well as its impact on moral values ​​and monotheism. The research method used is descriptive qualitative research, literature-based. The research results show that istighfar is not just a recommendation, but can also become an obligation in certain situations based on the maqāṣhid syarῑ'ah approach. Jasser Auda's systems approach, which focuses on "purposefulness", reveals that this hadith has flexibility in achieving the objectives of the Shari'a, both at the personal and social levels. Other results show the positive impact of istighfar on monotheistic, moral and economic values. Jasser Auda's systems approach highlights the importance of flexibility in understanding the context of istighfar according to modern times. It is concluded that with the maqāṣhid approach, istighfar is understood as part of efforts to achieve general benefit in Islam and remains relevant in the social, economic and cultural context in the modern era. Thus, istighfar not only has spiritual benefits but also social, moral and economic benefits.